The Internalization of Discipline Values in Daily Learning: A Case Study of First-Grade Elementary School Students - Sholiha Indah Rahayu; Yusrizal Yusrizal; Fatmawati Fatmawati (Institut of Shanti Bhuana, 2026)
This study aims to describe the internalization of discipline values in the daily learning activities of first-grade elementary school students. The research employed a qualitative descriptive approach conducted at SD Swasta PAB 29 Manunggal. The participants consisted of one first-grade teacher and five students selected purposively based on their active involvement in classroom activities. Data were collected through observation, semi-structured interviews, and documentation. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and technique triangulation as well as member checking. The findings reveal that the internalization of discipline values is implemented through five main aspects: teacher modeling, classroom management, rule enforcement and supervision, habituation, and guidance and reinforcement. Teacher modeling plays a fundamental role as students tend to imitate behaviors demonstrated by the teacher. Structured classroom management helps students understand learning routines and expected behaviors. Rule enforcement and consistent supervision ensure that students adhere to classroom norms. Habituation through repetitive daily activities fosters the development of disciplined behavior. In addition, guidance and positive reinforcement encourage students to maintain appropriate behavior and improve their self-regulation. Overall, the integration of these five aspects creates a systematic and continuous process in developing students’ discipline. The study contributes both theoretically and practically by providing insights into effective strategies for fostering discipline in early-grade elementary education through contextual and humanistic approaches.